2014
DOI: 10.1002/asia.201402146
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Particle Dynamics Simulation Study on Vesicles Self‐Assembled from Amphiphilic Hyperbranched Multiarm Copolymers

Abstract: Hyperbranched multiarm copolymers (HMCs) have been shown to hold great potential as precursors in self-assembly, and many impressive supramolecular structures have been prepared through the self-assembly of HMCs in solution. However, theoretical studies on the corresponding self-assembly mechanism have been greatly lagging behind. Herein, we report the self-assembly of normal or reverse vesicles from amphiphilic HMCs by dissipative particle dynamics (DPD) simulation. The simulation disclosed both the self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 100 publications
2
19
0
Order By: Relevance
“…4A). Lateral fusion of NPs during the longer period allowed for self-assembly would result in a particle structure enclosing the free fluorescein, as previously reported for amphiphilic HBPs [1,5,6,56]. This result supports our hypothesis that the particles formed polymer vesicles composed of a bilayer membrane and a hydrophilic interior.…”
Section: Preparation Of Larger Particles (Vesicles) and Controlled Resupporting
confidence: 91%
See 2 more Smart Citations
“…4A). Lateral fusion of NPs during the longer period allowed for self-assembly would result in a particle structure enclosing the free fluorescein, as previously reported for amphiphilic HBPs [1,5,6,56]. This result supports our hypothesis that the particles formed polymer vesicles composed of a bilayer membrane and a hydrophilic interior.…”
Section: Preparation Of Larger Particles (Vesicles) and Controlled Resupporting
confidence: 91%
“…4B and S5, and the particles with a self-assembly time of 48 h were generally much larger than the particles formed with a self-assembly time of 4 h. This result indicated that the size and likely the structure of the particles could also be tuned by varying the time of self-assembly in THF/PBS, which is interesting when designing particles for biomedical applications. We believe that these larger particles resulted from the lateral fusion of NPs during the longer time allowed for self-assembly, as reported elsewhere [1,5,6,56]. According to the literature, these particles would be classified as hyperbranched polymer vesicles composed of a bilayer membrane and hydrophilic interior, which have previously shown their potential as DDSs [5,57], but more studies are required to confirm this hypothesis.…”
Section: Encapsulation and Release Study Using Peg01-npssupporting
confidence: 55%
See 1 more Smart Citation
“…The resulted hyperbranched polymer vesicles were termed as branched-polymersomes (BPs) 29 and have unique properties such as good stability, low permeability, giant and easily tuned vesicle size, appealing solution behaviours, and facile tailorability of the properties. Extensive studies are still needed for elucidating the mechanism for the formation of BPs and verifying the results obtained using dissipative particle dynamics (DPD) simulations 30 .…”
mentioning
confidence: 97%
“…The simplest type of them is to regard HBPs/HBMCs as the monodisperse polymers. For example, in the dissipative particle dynamics (DPD) simulations on the self-assembly of amphiphilic HBMCs, all the polymers have the same predetermined hyperbranched structure in the simulation box 41 42 . This monodisperse model is quite simple but is far from the fact.…”
mentioning
confidence: 99%